Analisis Respons Peserta Didik Tunagrahita terhadap Media Huruf Timbul dan Video Animasi Berbasis Artificial Intelligence dalam Pembelajaran Huruf Vokal - Eylen Yossi Siagian; Apri Ulita; Enjelina Pitri Simamora; Johannes Bagas Sitorus; Tri Lande (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Students with intellectual disabilities require concrete and engaging learning media. This study analyzes the responses of students with intellectual disabilities to raised letters and Artificial Intelligence (AI) based animated videos in learning vowels. The method used is descriptive qualitative with a case study approach. The subjects of the study were three students with mild intellectual disabilities at SD Negeri 066667 Medan, consisting of two fifth-grade students and one fourth-grade student. Data were collected through observation, documentation, and field notes, then analyzed using the Miles and Huberman model. The results showed that all students responded positively to the AI-based animated videos, which increased their attention and learning engagement. However, responses to raised letters varied: fourth-grade students were more responsive to tactile media, while fifth-grade students were more interested in audio-visual media. These findings indicate that the learning styles of students with intellectual disabilities are individual, so the use of media needs to be adjusted to the needs of each student.